(3UQa GdQjM GdefJf Yf eSJYed GdJfJfs - (3OGhO Hf SdjeGf GdHZOGOj GdfbTHfOj GdNGdOqj GdTGaYqj, GHf LQLjS,J (B1299 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi fRgfG Yf fJf GdJJf hbPQg , hfRgfG ai QjGV GdPcQ YfO EfbHGV GdUOQ HJhajbg s
(3BNQgG (B:s
(3YGafG Gddg hEjGce ef gPG GdOGA , hJOGQcfG ef QMeJg hJhajbg HGdOGA , hGdMeO ddg Cgd GdMeO hGdKfGA HdG EfbWGY hdG EfKfGA hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjeG GfJgi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B332 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B136s
Keywords: (3Gdabg GdESdGejs